Strategies for sustainable upgrading in global value chains: The Tunisian olive oil sector - Jan Grumiller; Hannes Grohs; Werner Raza; Cornelia Staritz; Bernhard Tröster (Austrian Foundation for Development Research (ÖFSE), 2018)
This policy note presents policy recommendations for a sustainable development strategy for the Tunisian olive oil sector in the context of the ongoing negotiations on the Deep and Comprehensive Free Trade Agreement (DCFTA) between Tunisia and the EU. Against the backdrop of increasing local value added and ecological constraints, a sector development strategy should primarily focus on exploiting functional and product upgrading potentials in the EU and other end markets instead of increasing low value bulk exports.
Keywords: 330